Analyzing the Potential of Cross-Border Ecotourism in Entikong from an Ecotourism Political Economy Perspective - Fuzy Firda Zhan; Wahyudin, Eri (International Journal of Economics, Business and Innovation Research, 2025)
Cross-border tourism is a sector that is increasingly being considered by the Indonesian and Malaysian governments, especially in the West Kalimantan-Sarawak border region through the Entikong State Border Post. Due to its strategic location, this region has great potential for developing cultural tourism, ecotourism, and trade that can benefit both countries. This study uses an ecotourism political economy approach as a critical analytical tool to analyze the potential for cross-border ecotourism development in Entikong using ecotourism political economy theory as an analytical tool. The method used to analyze this study is descriptive qualitative. Data were collected and analyzed using a narrative literature review method. This study found that the potential for cross-border ecotourism development in Entikong from an ecotourism political economy perspective is a novelty, and it can be seen from four aspects: environmental ecological potential, capital economic potential, sociocultural potential, and political potential of power relations. Therefore, the Indonesian and Malaysian governments need to develop a technical cooperation framework and cross-border tourism policies that are not only economically oriented but also consider social and ecological sustainability. Involving local governments and communities in cross-border policy negotiations is crucial.